Self-management programs conducted within a practice setting: Who participates, who benefits and what can be learned? - Packer, Tanya; Boldy, D.; Ghahari, Setareh; Melling, L.; Parsons, Richard; Osborne, R. (Elsevier Ireland Ltd, 2012)
Objective: To investigate the impact of generic and diabetes-specific self-management programs offered in a real world context. Methods: A quasi-experimental design with 12-week follow-up compared Living with a Chronic Condition and Living with Diabetes. Self-report data collected included: Self-management Knowledge and Skills; Health Related Quality of Life (HRQOL); Depression; Social Isolation; Loneliness; Self-efficacy; and Health Behaviours. Results: Participants (N = 458) in the two programs differed on almost all baseline measures. Both demonstrated statistically significant improvements in Self-management Knowledge and Skills, as well as reductions in depression. In addition to younger age, low HRQOL, high self-efficacy and Positive and Active Engagement in Life, were the clinical factors most likely to lead to improvements in HRQOL and self-efficacy. Changes in different characteristics predicted different outcomes. Conclusion: Both generic and disease-specific programs led to improved outcomes, despite the two programs attracting significantly different participants. Referral patterns also differed but GP referral rates were low for both. Practice implications: Positive participant outcomes can be achieved in real life clinical settings. While younger people with a positive attitude may appear to gain more, it is important to encourage people from low socio-economic status to enter these programs so that social inequalities in health are not worsened.